(untitled) (Praxis Educativa, 2015)
This paper presents pedagogy postgraduate courses at the Autonomous National University of Mexico (UNAM), in its current model. It revises general aspects of its structure, within the framework of the system of postgraduatestudies at this university and explains the pedagogic and educationalbases that support contents, organization, and related practices. Taking into account the General Regulation of Postgraduate Studies at the UNAM, this postgraduate course resumes the orientations of curricular flexibility and tutorials and takes responsibility for teacher training, central axis of the program, from a multirreference perspective.